Perioperative Shift in Respiratory Bacterial Colonization and Post-operative Pneumonia in Spine Surgery Patients Requiring Intensive Care: A Prospective Cohort Study - Agil Murthala; Rieva Ermawan; Rhyan Darma Saputra (HM Publisher, 2026)
Spine surgery frequently requires post-operative intensive care and endotracheal intubation, both of which predispose to nosocomial respiratory infection, yet the perioperative dynamics of airway bacterial colonization in spine surgery patients and their relationship to pneumonia are poorly characterised, particularly in Indonesian practice. We conducted a prospective cohort study of 34 patients undergoing elective spine surgery with post-operative care in the ICU/PICU of Dr. Moewardi Regional General Hospital, Surakarta. Paired pharyngeal swab cultures were obtained at induction and during intubated intensive care, with disk-diffusion susceptibility testing. Post-operative pneumonia was defined by chest-radiographic infiltrate plus leukocytosis or leukopenia. Associations were assessed using Fisher exact tests, Haldane-Anscombe corrected odds ratios, rank correlation, and Cohen's h, with 95% confidence intervals. Most patients underwent decompressive laminectomy with posterior spinal fusion (76.5%). Pre-operative pathogenic colonization was present in 21/34 patients (61.8%; 95% CI 45.0-76.1). The flora shifted toward pathogens post-operatively, with Staphylococcus aureus rising from 6 to 9 isolates (+50%), Acinetobacter baumannii from 2 to 4, and new Serratia marcescens and Proteus mirabilis; ciprofloxacin resistance predominated and increased. Post-operative pneumonia occurred in 1/34 patients (2.94%; 95% CI 0.52-14.92). Pre-operative colonization was not associated with pneumonia (Fisher p=1.000; OR 1.98, 95% CI 0.07-52.17). ICU stay >48 h and endotracheal-tube duration >24 h were each strongly rank-correlated with pneumonia (rho=0.696), although, given a single event, the exact test was not significant (p=0.059). Intensive-care exposure rather than pre-operative colonization characterised pneumonia risk, while resistant Gram-negative organisms emerged perioperatively. Duration-focused prevention and antimicrobial stewardship are warranted in orthopedic critical care.